2020
DOI: 10.1016/j.ejrad.2020.109114
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for automated exclusion of cardiac CT examinations negative for coronary artery calcium

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Alternatively, the identification of CCTA without coronary artery calcification can be used to help prioritize work lists, by identifying scans that can be reviewed less urgently [ 66 ]. These techniques can also be used to expand the capabilities of CCTA, for example, to identify lesion-specific ischemia from conventional anatomical images [ 53 ].…”
Section: Ai In Cardiovascular Ctmentioning
confidence: 99%
“…Alternatively, the identification of CCTA without coronary artery calcification can be used to help prioritize work lists, by identifying scans that can be reviewed less urgently [ 66 ]. These techniques can also be used to expand the capabilities of CCTA, for example, to identify lesion-specific ischemia from conventional anatomical images [ 53 ].…”
Section: Ai In Cardiovascular Ctmentioning
confidence: 99%
“…Subsequently, only candidate lesions in the vicinity of the coronary arteries were classified using a neural network that combines spatial coordinate features with features from the segmentation CNN. Van den Oever et al [20] proposed an approach that employs a CNN to segment CAC by analyzing image slices in three orthogonal directions and thereafter, combines them to obtain the final segmentation. The evaluation showed that due to the absence of false negative predictions, the method could be used to exclude scans without CAC to relieve the workload of radiologist.…”
Section: Coronary Calcium Scoring In Cardiac Ctmentioning
confidence: 99%

AI for Calcium Scoring

van Velzen,
Hampe,
de Vos
et al. 2021
Preprint
“…The identification of calcified plaque on CT using deep learning has been widely studied, particularly on non-contrast images, but the automatic identification of non-calcified and high-risk plaque subtypes is more challenging [59]. Recently, a deep learning algorithm that identified CCTA without calcification has been proposed as a method to help prioritize work lists [60]. Further advancements in machine learning to automate plaque analysis will reduce the time to perform this analysis and increase its application in clinical practice.…”
Section: Future Developments -Radiomics and Machine Learningmentioning
confidence: 99%